Location Covering Models History, Applications and Advancements - Church, Richard L. (Advances in Spatial Science, The Regional Science Series,, 2018)
This book provides a thoughtful and rigorous guide to coverage modeling, reviewing essential models, solution approaches, and related applications. Since the early developments of the Location Set Covering Problem and the Maximal Covering Location Problem, models based upon some form of coverage have been extended and applied in a number of areas, helping to improve services offered to citizens of large cities and regions. Examples include trauma care services, transit systems design, cell tower location, and many others. The book not only describes the strengths and weaknesses of currently available models, but also presents details on major developments, including solution procedures and applications, making it well suited both as a reference text and a textbook for graduate level courses.